‘Hot phase’ non‐dilated left ventricular cardiomyopathy with atypical onset and recurrence: a case report - Nicola Gonano; Vincenzo Nuzzi; Daniela Pavan; Rita Piazza; Rosa Pecoraro; Alessandro Altinier; Rossana Bussani; Gianfranco Sinagra; Marco Merlo (ESC Heart Failure)
Abstract Non‐dilated left ventricular cardiomyopathy (NDLVC) is a newly categorized cardiomyopathy phenotype includingseveral aetiologies with a linking characteristic represented by the normal left ventricular volume. Inflammatory heart disease (InHD) is a heterogeneous process with variegate clinical manifestations, sometimes in overlap with NDLVC. A 26‐year‐old woman was admitted forcomplete heart block (CHB) and persistently raised troponin. Echocardiography and coronary angiography were normal. Extensive oedema and late gadolinium enhancement was found at cardiac magnetic resonance. Endomyocardial biopsy showed no signs of active myocarditis. Steroid therapy was started with restoration of atrioventricular conduction but subsequently the patient experienced a mild recurrence with a new troponin relapse. Genetic test was negative for mutations related with the clinical scenario. In this case of NDLVC with InHD the precise diagnostic work‐up, including genetic test, was crucial for diagnostic, prognostic andtherapeutic purposes. Multimodality approach is crucial to detect and treat possible recurrences.